Recent advances on research of native prawn Macrobrachium americanum (Decapoda: Palaemonidae) with aquaculture and conservation purposes - Yuneisy M. Agüero-Fernández; Miriam V. Martín-Manzo; Maritza L. Soberanes-Yepiz; Marcelo U. García-Guerrero; Yuniel Méndez-Martínez; Luis H. Hernández-Hernández; Laura S. López-Greco; Edilmar Cortés Jacinto (Marine and Fishery Sciences, 2022)
where good management practices on aquaculture are mandatory. The economic and ecological importance of prawns of the Genus Macrobrachium cause an impact at a global level involving economic, academic and social aspects. Macrobrachium americanum appears as one of the genus species with high nutritional value and an economic demand in the national and international markets, as well as a vital income for fisherman and producers of this species. For researchers, it is a challenge to find solutions to culture and propose conservation measures for M. americanum with emphasis on development, nutrition and reproduction. Although there are scientific studies supporting the economic importance of this species, our knowledge about its cultivation, reproduction and conservation is limited. This paper summarizes the latest studies made in cooperation with M. americanum in research lead by the Centro de Investigaciones Biológicas del Noroeste, Mexico. After several years of continuous research, it is considered that those efforts have produced useful information for the sustainable exploitation, conservation and basic management practices of this species.